2019
DOI: 10.1590/fst.02818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot air drying on quality characteristics and physicochemical properties of bee pollen

Abstract: The aim of this study was to investigate the effect of hot air drying on quality characteristics, physicochemical properties, morphological structure and organoleptic characteristics of bee pollen, and compute the effective moisture diffusivity and activation energy during hot air drying of bee pollen. Bee pollen samples were dried at 40, 45, 50, 55 and 60 °C. Effective moisture diffusivity (D eff) values ranged from 1.38 × 10 −10 to 4.00 × 10 −10 m 2 /s, and the activation energy (E a) was found to be 42.96 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
(30 reference statements)
7
24
0
Order By: Relevance
“…No statistically significant difference was noted between the packaged and unpackaged bee pollen products in terms of physicochemical properties except for the titratable acidity (p < 0.05). The ash contents of bee pollen samples found in this study were similar to those reported by Isık et al (2019), which ranged from 2.14-2.18 g/100 g in hot air dried bee pollen samples. Bárbara et al (2015) reported similar results indicating that the mean moisture, ash, pH, titratable acidity levels of 21 bee pollen (Melipona mandacaia) samples collected from two different regions of Bahia and Brazil were 36.0%, 4.9%, 3.49, and 146 meq•kg −1 , respectively.…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…No statistically significant difference was noted between the packaged and unpackaged bee pollen products in terms of physicochemical properties except for the titratable acidity (p < 0.05). The ash contents of bee pollen samples found in this study were similar to those reported by Isık et al (2019), which ranged from 2.14-2.18 g/100 g in hot air dried bee pollen samples. Bárbara et al (2015) reported similar results indicating that the mean moisture, ash, pH, titratable acidity levels of 21 bee pollen (Melipona mandacaia) samples collected from two different regions of Bahia and Brazil were 36.0%, 4.9%, 3.49, and 146 meq•kg −1 , respectively.…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…For the preservation of freshly collected pollen, different drying techniques-hot-air drying, freeze-drying, microwave drying, vacuum drying, and microwave-assisted vacuum drying, are used [58,61,62,64,[67][68][69] (freeze-drying and hot-air drying are most commonly applied [58,61,62,[67][68][69]). Drying the pollen with hot air is recommended at the temperature of 40 • C, while at higher temperatures the physicochemical properties, morphological structures, and organoleptic characteristics of pollen are disturbed [62]. For example, drying the pollen samples at 60 • C reduced the amounts of protein and vitamin C by 43.7% and 31.5%, respectively, changed the pollen colour (∆E value 9.19 ± 2.11), and significantly decreased the sensory attributes (visual appearance, colour, and odour) of the dried pollen compared to the fresh one [62].…”
Section: The Influence Of Drying Techniques On the Quality Of Bee-colmentioning
confidence: 99%
“…Drying the pollen with hot air is recommended at the temperature of 40 • C, while at higher temperatures the physicochemical properties, morphological structures, and organoleptic characteristics of pollen are disturbed [62]. For example, drying the pollen samples at 60 • C reduced the amounts of protein and vitamin C by 43.7% and 31.5%, respectively, changed the pollen colour (∆E value 9.19 ± 2.11), and significantly decreased the sensory attributes (visual appearance, colour, and odour) of the dried pollen compared to the fresh one [62]. Furthermore, Collin et al [66] pointed out that only the drying treatment of pollen at 30 • C, or for a short time at 40 • C, can be effective at avoiding the synthesis of dimethyl sulphide (pollen is rich in 5 -methylmethionine), undesirable aldehydes, and furan compounds, and preventing the loss of the desirable monoterpenic compounds.…”
Section: The Influence Of Drying Techniques On the Quality Of Bee-colmentioning
confidence: 99%
“…The physicochemical properties of bee-collected pollen can be affected both by processing techniques [7,11,[18][19][20][21] and storage conditions [22][23][24][25][26][27]. Pollen freshly collected by honeybees contains from 15% to 30% (w/w) of water.…”
Section: Introductionmentioning
confidence: 99%